Tools of characters creating in the novel by Lyuko Dashvar «Smell of Meat» - Гурдуз, Катерина Олександрівна; Пінігіна, Юлія Геннадіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The study was performed in the mainstream of contemporary literary studies. It is associated with observation of artistic features of the psychology of women’s prose. The object of scientific search is the novel «Smell of Meat» by Lyuko Dashvar, who is one of the most brilliant Ukrainian writers of our time, the subject is complex system of characters modelling the in the novel. Psychologism in the novel by Lyuko Dashvar «Smell of Meat» has its own specifics and performs special functions. Creating expressive characters, the author fully reveals the artistic potential of portrait characteristics, subject details, landscapes, and interiors, which help to understand the author’s attitude and identify the stylistic originality of the work.